The efficacy of mycolic acid-enhanced PLGA nanoparticles for rifampicin delivery in tuberculosis treatment - Lemmer, Yolandy (University of Pretoria, 2025)
Dissertation (MSc (Biochemistry))--University of Pretoria, 2024.